The posterior reversible encephalopathy syndrome in HIV infection - Nightingale, Sam (BMJ Publishing Group, 2012)
Posterior reversible encephalopathy syndrome (PRES) is often associated with hypertension, however recent advances in the understanding of this condition have shown that endothelial dysfunction is responsible for much of the pathogenesis and the condition can occur in the absence of hypertension. This case describes a 32-year-old lady with untreated HIV infection who developed PRES at a normal blood pressure and without opportunistic infection or other conditions known to precipitate PRES. HIV, particularly when untreated, is associated with endothelial dysfunction and this may have been sufficient to cause PRES in this patient. To our knowledge this is the first case to describe PRES in HIV without uncontrolled hypertension, sepsis or other precipitating cause.